MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI BERMAIN MOZAIK ANAK USIA 5-6 TAHUN DI TK PKBM MELATI MUKTIJAYA KABUPATEN ROKAN HILIR - Sukesih, Sukesih; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Fine motor skills of children in kindergarten Tk Pkbm Melati Bed Muktijaya Rokan Hilir is still low due to lack of ability to mimic the shape, exploring the various media and activities, hold a pencil properly, in accordance with the pattern cutting and sticking with the right image. Under these conditions it is necessary efforts to improve fine motor skills of children is through play mosaic. The purpose of this study was to determine the fine motor skills of children through play mosaics, to know how to play the mosaic application, to determine whether to play the mosaic can improve fine motor skills of children and to determine the height increase occurs. This research is a classroom action research conducted in two (2) cycles. Data collection tool used in this study is in the form of sheets of observation and research subjects are children aged 5-6 years in kindergarten Tk Pkbm Melati Muktijaya consisting of 15 children 7 boys and 8 girls. Results from this study showed an increase from cycle I to cycle II. Improvement occurred, ie from before the action to the first cycle of 33.33%, the first cycle to the second cycle of 37.07%, and from the prior cycle to cycle II of 82.76%. From the results of this study concluded that through playing mosaic can improve fine motor skills of children aged 5-6 years in kindergarten Tk Pkbm Melati Bed Muktijaya Rokan Hilir.Keywords: Finemotor skills, play Mozaik